P04.55 Efficacy of Tumor Treating Fields (TTFields) and aurora B kinase inhibitor. (19th September 2018) - Krex, D; Bartmann, P; Temme, A; Schneiderman, R; Voloshin, T; Giladi, M; Kinzel, A; Kirson, E; Weinberg, U; Palti, Y
Abstract: Background: Tumor Treating Fields (TTFields) are an effective anti-neoplastic treatment modality delivered via noninvasive application of low intensity, intermediate frequency, alternating electric fields. TTFields is approved for the treatment of both newly diagnosed and recurrent glioblastoma. A promising approach to enhance the efficiency of TTFields is the use of drugs which extend metaphase-anaphase transition and telophase. Specifically, inhibitors or drugs interfering with components of the chromosomal passenger complex, in particular affecting Aurora B kinase, are potential candidates for combinatorial use with TTFields. The goal of the present study is to test the hypothesis that TTFields effect on tumor cells can be exaggerated by an additional inhibition of cytokinesis through chemical inhibition of Aurora B kinase. Material and Methods: Efficacy of the combined treatment of TTFields and Aurora B kinase inhibitors (AZD1152) was tested in two sets of experiments comprising glioma cell lines: U87-MG, U87-MG shP53 and U-251 in the first set, and U87-MG, and two primary glioblastoma cell lines (HT16360, HT18503) in the confirmatory set. TTFields (1.6 V/cm RMS, 200 kHz) were applied for 72 hours using the inovitro system. AZD1152 was added to the media in concentrations of up to 100 nmol/L. Cell counts, cell cycle and clonogenic potential were determined at the end of treatment. Formation of multinuclear cells was determined using microscopic images of cells stained with crystal violet. Results: The combined treatment of TTFields and AZD1152 led to a significant reduction in the number of U251, U-87 MG and U-87 MG shP53 cells (2-way ANOVA, p<0.001 in all three cell lines) as compared to each treatment alone. The overall effect taking into account, not just the cytotoxic effect at the end of treatment, but also the clonogenic potential, demonstrated a significant reduction in U87-MG, U87-MG shP53 and U-251 cells (2-way ANOVA, p<0.001 in all 3 cell lines) as compared to each treatment alone. Microscopy images of U87-MG and U87-MG shP53 cells stained with crystal violet after treatment, revealed high prevalence of multi nuclear cells in cells exposed to TTFields and AZD1152 (25nM) as compared to cells treated with AZD1152 (25nM) alone. Cells treated with TTFields and higher doses of AZD1152 (50-100nM) demonstrated increased rates of pyknosis. Data could be confirmed in primary tumor-cell lines. Conclusion: The results presented in this work demonstrate that the combination of TTFields and AZD1152 can be an effective treatment against glioma cells. Based on the above, there is a strong rational to continue exploring the potential of combining TTFields and AZD1152 in the clinical settings.